Realization of the Right of Inheritance: Problems of Legislation and Law Enforcement Practice - MUSSAYEVA, Inkar; BOZHKARAULY, Altai (Journal of Advanced Research in Law and Economics; Vol 9 No 7 (2018): JARLE Volume IX Issue 7(37) Winter 2018, 2019)
This article deals with topical issues of inheritance in the Civil Legislation of Kazakhstan. The characteristic features of inheritance adoption methods, the use of various methods of legal analysis in the process of such interpretation (on the example of texts of judgments of the Court of Kazakhstan) are analyzed. On the basis of the study, the author proposes to identify the legal-technical ways of accepting an inheritance, gives its definition, formulates the main characteristics of the legal analysis that constitute the legal-technical ways of accepting an inheritance.